Uric Acid Predicts Recovery of Left Ventricular Function and Adverse Events in Heart Failure With Reduced Ejection Fraction: Potential Mechanistic Insight From Network Analyses - Wang, Xiqiang; Fan, Xiude; Wu, Qihui; Liu, Jing; Wei, Linyan; Yang, Dandan; Bu, Xiang; Liu, Xiaoxiang; Ma, Aiqun; Hayashi, Tomohiro; Guan, Gongchang; Xiang, Yu; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background and Aims Heart failure with reduced ejection fraction (HFrEF) still carries a high risk for a sustained decrease in left ventricular ejection fraction (LVEF) even with the optimal medical therapy. Currently, there is no effective tool to stratify these patients according to their recovery potential. We tested the hypothesis that uric acid (UA) could predict recovery of LVEF and prognosis of HFrEF patients and attempted to explore mechanistic relationship between hyperuricemia and HFrEF. Methods HFrEF patients with hyperuricemia were selected from the National Inpatient Sample (NIS) 2016–2018 database and our Xianyang prospective cohort study. Demographics, cardiac risk factors, and cardiovascular events were identified. Network-based analysis was utilized to examine the relationship between recovery of LVEF and hyperuricemia, and we further elucidated the underlying mechanisms for the impact of hyperuricemia on HFrEF. Results After adjusting confounding factors by propensity score matching, hyperuricemia was a determinant of HFrEF [OR 1.247 (1.172–1.328); P < 0.001] of NIS dataset. In Xianyang prospective cohort study, hyperuricemia is a significant and independent risk factor for all-cause death (adjusted HR 2.387, 95% CI 1.141–4.993; P = 0.021), heart failure readmission (adjusted HR 1.848, 95% CI 1.048–3.259; P = 0.034), and composite events (adjusted HR 1.706, 95% CI 1.001–2.906; P = 0.049) in HFrEF patients. UA value at baseline was negatively correlated to LVEF of follow-ups (r = −0.19; P = 0.046). Cutoff UA value of 312.5 μmmol/L at baseline can work as a predictor of LVEF recovery during follow-up, with the sensitivity of 66.7%, the specificity of 35.1%, and the accuracy of 0.668 (95% CI, 0.561–0.775; P = 0.006). Moreover, gene overlap analysis and network proximity analysis demonstrated a strong correlation between HFrEF and Hyperuricemia. Conclusion Lower baseline UA value predicted the LVEF recovery and less long-term adverse events in HFrEF patients. Our results provide new insights into underlying mechanistic relationship between hyperuricemia and HFrEF.